Keterkaitan Indeks Harga Konsumen (IHK) Kelompok Bahan Makanan dengan Kelompok Makanan Jadi, Minuman, Rokok, dan Tembakau di Indonesia Tahun 2014-2019 (Pendekatan Vector Error Correction Model) - Azima, Lira; Astuti, Erni Tri (Universitas Sebelas Maret, 2022)
Pricing a commodity depends on the price of other commodities. As the largest contributor to inflation, the pattern of price movements in CPI of prepared food, beverages, cigarette, and tobacco group is inseparable from CPI of foodstuff group as the raw material for that group. This condition indicates that in analyzing the pattern of price movements of a commodity, it cannot be separated from the influence of other commodities. The aims of the study is to examine the linkages between CPI of foodstuff group and CPI of prepared food, beverages, cigarette, and tobacco group, also its response and contribution when there is shock during January 2014 until December 2019 in Indonesia using Vector Error Correction Model (VECM). The results suggest that in long-term CPI of prepared food, beverages, cigarette, and tobacco group has positive effect on CPI of foodstuff group. Impulse Response Function (IRF) shows that shocks to CPI of foodstuff group is positively responded by CPI of prepared food, beverages, cigarette, and tobacco group, and vice versa. In addition, Forecast Error Variance Decomposition (FEVD) show that the variation of CPI of prepared food, beverages, cigarette, and tobacco group are dominated by contribution of CPI of foodstuff group.Keywords : consumer price index, VECM, impulse response function, forecast error variance decomposition